2020
DOI: 10.1088/1755-1315/609/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Forest Typology as a Scientific and Methodological Basis for Environmental Studies and Forest Management

Abstract: Paper describes key elements of a genetic approach to classification of forest types – one of the original forest typological research directions in Russia summarizes the results of research over the hundred-year period of formation and development of this promising (from the point of view of sustainable management of natural resources) scientific direction. Authors provide a map of current forest type genetic classification use in the Russian Federation, and outline key perspective directions in the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Generalizing research results are shown in Figure 3. The research results are given in more detail in our earlier publications [7,24,26]. This report is generalizing.…”
Section: Resultsmentioning
confidence: 81%
“…Generalizing research results are shown in Figure 3. The research results are given in more detail in our earlier publications [7,24,26]. This report is generalizing.…”
Section: Resultsmentioning
confidence: 81%
“…Natural classifications, including ones based on forest ecology and concepts of Sukachev's biogeocenosis, consider forest type from the point of view of spatial homogeneity of the characteristics (composition and structure) displayed by forest community components [15,16]. For these approaches, the forest type includes sites that are uniform in terms of characteristics (composition and structure), so the forest type is determined on the basis of the forest site spatial uniformity criteria [5,12]. In genetic classifications, the spatial uniformity criteria for forest sites are replaced with criteria that determine similarity in genesis, dynamics, and development (i.e., temporal uniformity) [5,30,31] (Table 1).…”
Section: Russian Forest Ecological Classificationmentioning
confidence: 99%
“…The experience of the Russian forest typology is no less interesting and useful [5,12]. Ecological-silvicultural classification, phytocoenotic forest typology, genetic forest typology, and dynamic forest typology are actively used in modern forestry in the Russian Federation.…”
Section: Introductionmentioning
confidence: 99%
“…Potential vegetation is represented by various types of southern taiga forests, among which pine forests with birch and larch in the composition predominate. The systematization of forest types is carried out on the basis of geographical and genetic typology [9,10]. A brief description of the forest types is given in the catalog [8].…”
Section: Study Areamentioning
confidence: 99%